Os reflexos de Bolonha e a América Latina: problemas e desafios - MELLO, Alex Bolonha Fiúza de (2015)
This paper describes the Bologna Process, presents its evolution and analyzes the progress of its implementation in Europe and the diffculties it has faced. It provides a detailed analysis of the objections to the process itself and to its uncritical application in other parts of the world, especially in Latin America. The main criticism of Bologna is that the international agencies have issued guidance that directly or indirectly delegate the function of main provider of higher education, traditionally performed by the State, to the private sector. Bologna reforms have affected everything from the legal regime of the institutions and of the teaching careers to public funding and a new accreditation system.